2017
DOI: 10.1007/s13197-016-2476-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous improvement in solvent permeability and deacidification of soybean oil by nanofiltration

Abstract: In this paper, soybean oil deacidification and hexane removal using laboratory scale solvent resistance nanofiltration membranes based technique is presented. Composite nanofiltration membranes made of different polymers poly(vinylideneflouride) (PVDF), polydimethylsiloxane (SI), polycarbonate (PC), and glycerol were tested to remove the hexane and free fatty acid (FFA) from soybean oil/hexane miscella (oil feed solution 10, 25, and 35% w/w) at 20 bar of transmembrane pressure and 30°C, in a dead-end filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In contrast, the rejection of FFA shows a low value, with the highest rejection only 16.39%. FFA has a molecular weight of 300 Da, which is smaller than the membrane pore [18,24]. The low value of FFA rejection also confirms a low selectivity of the membrane.…”
Section: Effect Of Feed Composition On Phospholipid and Ffa Rejection Ratesmentioning
confidence: 92%
“…In contrast, the rejection of FFA shows a low value, with the highest rejection only 16.39%. FFA has a molecular weight of 300 Da, which is smaller than the membrane pore [18,24]. The low value of FFA rejection also confirms a low selectivity of the membrane.…”
Section: Effect Of Feed Composition On Phospholipid and Ffa Rejection Ratesmentioning
confidence: 92%
“…On the contrary, there was no appreciable selectivity for tocopherols and tocotrienols while processing undiluted and hexane‐diluted palm oil (Arora et al., 2006). Similarly, studies with acetone‐palm oil‐palmitic acid model miscella showed that the NF membranes (300‐500 Da) rejected palmitic acid in the range of 56‐86% (Ismail & Ghazali, 2018), contradicting preferential FFA permeation reported in several other real and model hexane‐oil systems (Firman et al., 2013, 2017; Raman et al., 1996). These results suggest that the typical composition of crude vegetable oils, as well as the solvent, could play a role in the relative permeation of these minor compounds.…”
Section: Membrane Technology Applications In the Refining Processmentioning
confidence: 98%
“…In another study (Firman et al., 2013), a lab‐cast PDMS membrane displayed an oil rejection of 80% and FFA reduction of 40% (selectivity ∼1.85), maintaining a higher miscella flux of 20.3 L/m 2 /h, while processing a degummed soybean oil miscella (25% oil with 0.5% FFA). To facilitate FFA permeation, polycarbonate was incorporated to the PDMS active layer (Firman et al., 2017) and the induced hydrophilicity improved the deacidifying performance (selectivity ∼2.43) without practically affecting the desolventizing efficiency (Ro 79%; 19.3 L/m 2 /h).…”
Section: Membrane Technology For Solvent Recoverymentioning
confidence: 99%
“…It has to be done in a very tightly closed system since the extract is as volatile as the solvent. Alternatives for removing FFA from vegetable oils that are still under development include catalytic esterification as reported by Habaki,et al in [18], enzymatic esterification as reported by Wang,et al in [19], enzymatic amidation as reported by Wang,et al in [20], membrane separation as reported by Azmi, et al in [21] and Firman, et al in [22], deep eutectic ionic liquid extraction as reported by Zullaikah,et al in [23] and Zahrina,et al in [24], and liquid-liquid extraction using volatile organic solvents, which is known as solvent extraction.…”
Section: Introductionmentioning
confidence: 99%